2008
DOI: 10.1146/annurev.biophys.36.040306.132651
|View full text |Cite
|
Sign up to set email alerts
|

Nanobiotechnology and Cell Biology: Micro- and Nanofabricated Surfaces to Investigate Receptor-Mediated Signaling

Abstract: Advances in microfabrication and nanofabrication are opening new opportunities to investigate complicated questions of cell biology in ways not before possible. In particular, the spatial regulation of cellular processes can be examined by engineering the chemical and physical environment to which the cell responds. Lithographic methods and selective chemical modification schemes can provide biocompatible surfaces that control cellular interactions on the micron and submicron scales on which cells are organize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(108 citation statements)
references
References 90 publications
0
108
0
Order By: Relevance
“…In spite of the porosity of the electrospun mats, they must be considered as a two dimensional substrates with respect to cell culture since inter-fiber spaces do not allow cell invasion of the three dimensional fiber structure. Cell-substrate interaction mediated by proteins adsorbed from the culture medium is crucial to control chondrocyte adhesion, proliferation and consequently gene expression in monolayer culture [5,[47][48]. It has been shown that nano-fibrilar substrates allow viable and proliferative chondrocyte culture [32,49].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the porosity of the electrospun mats, they must be considered as a two dimensional substrates with respect to cell culture since inter-fiber spaces do not allow cell invasion of the three dimensional fiber structure. Cell-substrate interaction mediated by proteins adsorbed from the culture medium is crucial to control chondrocyte adhesion, proliferation and consequently gene expression in monolayer culture [5,[47][48]. It has been shown that nano-fibrilar substrates allow viable and proliferative chondrocyte culture [32,49].…”
Section: Discussionmentioning
confidence: 99%
“…We and others demonstrated the versatility of patterned ligands that confine and activate receptors in micrometer-size regions so that the spatially regulated cellular responses can be monitored (for review, see ref. 16). An important feature of patterned lipid bilayers is that proteins do not adhere nonspecifically to the lipid regions: anti-DNP IgE-Fc RI binds selectively to these regions only because DNP-cap-PE is incorporated in the bilayers (17).…”
Section: Discussionmentioning
confidence: 99%
“…Another great advantage of the FCS is the possibility to accurately quantify local measurements of molecular mobility on diVerent temporal scales. Among the diVerent nanotechnologies applied on biomembranes (Torres et al 2008), the ones combining single nanometric aperture technology with FCS have great potential as recently demonstrated (Edel et al 2005;Moran-Mirabal et al 2007;Samiee et al 2006;Wenger et al 2006b). Indeed, these approaches preserve the FCS temporal resolution while providing a subwavelength spatial resolution.…”
Section: Biological Applicationsmentioning
confidence: 99%